25. INPATIENT TREATMENT COSTS OF PATIENTS WITH DRUG-RESISTANT TUBERCULOSIS AT THE NATIONAL LUNG HOSPITAL IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: This study aims to describe the inpatient treatment costs and cost structure of patients with drug-resistant tuberculosis at the National Lung Hospital in 2024.Subjects and methods: A cross-sectional descriptive study using retrospective data from medical records and hospital invoices of patients treated in 2024. The total number of inpatients with drug-resistant tuberculosis during the year was 629 patients.Results: The average total treatment cost per patient was VND 35,170,000. The highest cost were non-tuberculosis medications (38%), then laboratory tests (21.6%), and hospital bed-days (17.3%). Health insurance covered 61.6% of the total cost, while medical out -of- pocket cost accounted for 38.4%.Conclusion: The treatment cost of drug-resistant tuberculosis is considerably high, particularly due to the expenses for non-tuberculosis medications, laboratory testing, and hospital stays.
Keywords: Treatment cost; drug-resistant tuberculosis.